Integrating Perceived University Support and Theory of Planned Behavior in Determining Entrepreneurship Intention among Student - Siregar, Jonathan Lampatar; Siregar, Veronika Angel; Rahmiati, Filda; Daniela, Lerissa; Ramananda, Dimaz (Fakultas Ekonomi dan Bisnis Universitas Samudra, 2024)
Based on the Theory of Planned Behavior, this study investigates how perceived university support influences entrepreneurship intention through the mediating variables of attitude, subjective norms, and perceived behavioral control. Using a quantitative approach with 188 Generation Z student respondents from Jakarta, data was collected via online questionnaires and analyzed with SEM using SmartPLS 4. The results show that perceived university support significantly affects attitude toward behavior, subjective norms, and perceived behavior control. However, its impact on entrepreneurship intention is only significant when mediated by attitude and perceived behavioral control, while subjective norms show no significant indirect effect.